Hampering Factors of English Department Students’ Speaking Skill in Malang - Dini Kurnia Irmawati (Jurnal VOK@SINDO, 2016)
Having good ability in speaking will positively benefit students majoring in English Department in their future career. Being able to speak English well will strengthen their identity as English Department students. However, not all of them are able to speak in English well for communication. Thus, the researcher intends to investigate what kinds of hampering factors that apparently make English Department students hard to speak in English. This study is done qualitatively. The subjects of the study cover 364 students of University of Brawijaya, State University of Malang, and Kanjuruhan University. The instruments used are questionnaire, interview guide and observation sheet. The findings show that the most hampering factor of speaking skill in terms of teaching and learning activity is lack of assignment that makes the students do not get sufficient time to practice. In terms of learning materials, too difficult materials have bevome the most hampering factor for them to speak up. Next, in relation to lecturer’s personality, a lecturer who is too serious is the highest reason why they do not speak up actively. Then in terms of the use of English as a medium of instruction, the most hampering factor for the students is lack of the use of English in class. The next hampering factor related to feedback given is the ways how the lecturers give feedback which make the students embarrased. It is expected that the findings of this study can help lecturers to help students improve their speaking skill much better by designing better curriculum and syllabus, applying more communicative strategies in teaching, and creating more helpful atmosphere during the teaching and learning activities.